Istilah-Istilah Sesaji Ritual Sedekah Gunung Merapi di Desa Lencoh, Kecamatan Selo, Kabupaten Boyolali (Kajian Etnolinguistik) - Makrifah, Suci; Fateah, Nur (Sutasoma : Jurnal Sastra Jawa, 2019)
This research discusses terms offerings of the alms ritual of Mount Merapi in Lencoh Village, District of Selo, Boyolali Regency. The purposes of this research are (1) to describe kind the terms offerings of the alms ritual of Mount Merapi in Lencoh Village, Boyolali; (2) to explain the lexical and cultural meaning of the terms offerings of the alms ritual of Mount Merapi in Lencoh Village, Boyolali; (3) to explain reflection of local wisdom in terms offerings of te alms ritual of Mount Merapi in Lencoh Village, Boyolali. This research uses an ethnolinguistic approach and a qualitative descriptive approach. Data in this research was collected using etnographic methods with observation and interview techniques. Analysis of the data in this research using distributional method, method of padan and ethnosains to the terms offerings alms ritual of mountain . The results showed that first, the terms of offerings in the alms ritual of Mount Merapi consists of words and phrases. Second, the terms offerings of the almsritual of Mount Merapi classified based on lexical meaning and cultural meaning. Third, local wisdom that found in the terms offerings of the alms ritual of Mount Merapi is cultural wisdom that acquired through life experience and or passed down from generation to generation as a guideline for activities. Keywords: form of terms, alms of mountain, meaning, local wisdom, etnolinguistic